Self Recoded Video and diary Wrtiting Practices as a Way to Improve Higher Education Students’ English Speaking Skills - nita henita koesoemah (Jurnal Bahasa Inggris Terapan, 2020)
ABSTRACT Writing and Speaking are the productive Skills of a language. although higher education students have learned English for years in primary and secondary schools, many of them do not find it easy to speak English in their college years while they will need English during and after they graduate. To improve their English, especially speaking skill, self video recording and diary writing practice was carried out. This study was to analyze the effect of Self Recorded Video and Diary Writing on the improvement of English speaking skill of higher education students. The focus of this research is on four speaking skill categories; Pronunciation, Vocabulary, Grammar and Fluency. to get the answer error analysis is used and the result is presented using descriptive method. The data are students’ self recorded videos and diary writing were carried out once a week once a week in one semester. The result obtained is that self-recorded video and diary writing can improve student speaking skills especially in fluency, pronunciation and vocabulary. Key words: fluency, self-recorded video, diary writing, error analysis, descriptive method